2012
DOI: 10.1021/jp307305q
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Photoelectrochemical Properties of Chalcopyrite AgInS2 Nanoparticles Size-Controlled with a Photoetching Technique

Abstract: Size-selective photoetching enabled precise size control of chalcopyrite AgInS 2 nanoparticles in a basic aqueous solution containing ammonia by selecting the wavelength of monochromatic irradiation light in the range between 650 and 520 nm. The energy gap of the photoetched particles was enlarged from 1.8 to 2.4 eV with a decrease in particle size from 5.1 to 2.7 nm due to the quantum size effect, while the crystal structure and chemical composition of the particles were unchanged after the photoetching proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…Ternary AgInS 2 has a distinctive absorption in the visible and near-infrared regions because of its large absorption coefficient and its band gap energy between 1.87 and 2.03 eV, and it is considered one of the potential candidates for promising applications in photovoltaic and photocatalytic fields [16,17]. Various preparation methods for the preparation of AgInS 2 have been reported, such as thermal decomposition [18,19], hot-injection method [20] and hydrothermal method [21]. Coupling of AgInS 2 and TiO 2 NTs would be a perfect strategy to improve the visible light photoelectrochemical property of TiO 2 NTs.…”
Section: Introductionmentioning
confidence: 99%
“…Ternary AgInS 2 has a distinctive absorption in the visible and near-infrared regions because of its large absorption coefficient and its band gap energy between 1.87 and 2.03 eV, and it is considered one of the potential candidates for promising applications in photovoltaic and photocatalytic fields [16,17]. Various preparation methods for the preparation of AgInS 2 have been reported, such as thermal decomposition [18,19], hot-injection method [20] and hydrothermal method [21]. Coupling of AgInS 2 and TiO 2 NTs would be a perfect strategy to improve the visible light photoelectrochemical property of TiO 2 NTs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, disappearance was not significant when the TiO 2 substrate with Ag 32 was left for 30 min in the dark. 40,41 Since the absorption edge of those QDs also depends on the particle size, it can be controlled by self-oxidation of QDs at an appropriate irradiation wavelength. The injected electrons may be accepted by ambient oxygen or released Ag + to give small Ag particles as is the case for the photooxidation of plasmonic Ag nanoparticles.…”
mentioning
confidence: 99%
“…Figure 1 summarizes the size-dependent E g reported for several kinds of semiconductor particles with a spherical shape. [16][17][18][19][20][21][22] In each case, E g was remarkably enlarged with a decrease in particle size due to the quantum size effect when the particle size became smaller than twice the effective exciton Bohr radius of the corresponding bulk semiconductor. Considering the strong size dependence of E g , it is concluded that narrowing the size dispersibility is required for precisely controlling the photoelectrochemical properties of semiconductor nanoparticles as a function of their size.…”
Section: Size-dependent Electronic Energy Structure Of Semiconductor mentioning
confidence: 97%
“…The sizeselective photoetching technique has been widely used to control the size of quantized nanoparticles such as ZnO, 29 ZnS, 30 CdS, 26,27,31 CdSe, 32 CdTe, 33 InP, 34 InGaN, 35 and AgInS 2 nanoparticles. 21 However, being different from the case of photoetching CdS particles, an additional complexing agent such as NH 3 was necessary to successfully complete size-selective photoetching of AgInS 2 nanoparticles, because Ag + ions released along with the photoetching formed an insoluble Ag 2 O passivation layer on the particle surface to prevent further photoetching of AgInS 2 . The photoetched AgInS 2 particles had the same crystal structure and the same chemical composition (Ag/In ratio) as those of the original particles.…”
Section: Size-dependent Electronic Energy Structure Of Semiconductor mentioning
confidence: 99%
See 1 more Smart Citation